Ultra-high temperature metamorphism in the Guaxupe Complex: a lower crust segment - Leme, Thais Guitzlaf [UNESP]; Beltran Navarro, Guillermo Rafael [UNESP]; Zanardo, Antenor [UNESP] (Soc Brasileira Geologia, 2020)
The area is located at the northern boundary of the Guaxupe Complex, which corresponds to the northern domain of the Socorro-Guaxupe Nappe, in the Southern Brasilia Orogen, close to the Varginha Shear Zone. This study integrates petrography, mineral chemistry, optimized geothermobarometry, and trace elements thermometry data, aiming to define and characterize the metamorphic conditions and the P-T path of the granulitic rocks from the northern portion of the Guaxupe Complex. In the area, the Guaxupe Complex consists predominantly of ortho-derived rocks represented by granulitic gneisses (orthopyroxene gneisses) of felsic to mafic composition with clinopyroxene, garnet, amphibole, biotite, and rare rutile. The calculated pressure and temperature conditions record metamorphic peak around 1,078 degrees C and 14.8 kbar, compatible with ultra-high temperature metamorphism conditions, marked by grt + cpx + opx + pl +/- qtz +/- rt mineral assemblages, and granulite facies re-equilibration in the sillimanite stability field at P-T conditions of 930 to 800 degrees C and 13.5 to 11.0 kbar. The results are compatible with deeper portions of the lower crust involved in a continental collision and suggest a clockwise P-T path, typical of crustal thickening zones, followed by near-isothermal decompression during tectonic exhumation.
Keywords: Southern Brasilia Orogen; Guaxupe Complex; Granulites; UHT metamorphism; lower crust